The Impact of Renewable Energy Consumption on Carbon Dioxide Emissions: Empirical Evidence from Developing Countries in Asia - Hasnisah, Azilah; Azlina, A. A.; Che Taib, Che Mohd Imran (International Journal of Energy Economics and Policy, 2019)
This empirical study examines the relationship between environmental quality, economic development, renewable and non-renewable energy consumption in 13 developingcountries in Asia. We use panel data in the period from 1980 to 2014 and panel cointegration, Fully Modified OLS and Dynamics OLS estimators are employed to test for cointegrationin the long-run. The study confirms the existence of the inverted U-shape EKC hypothesis in 13 Asia countries for both estimators with the increment of GDP per capita and conventionalenergy consumption decreasing the environmental quality. However, the empirical finding suggests that renewable energy consumption is insignificant in contributing to less pollution regardingCO2emissions. This study concludes that to comprehend betterthe potential factors affecting the CO2 emissions, the sampled countries can design a strategic plan to mitigate the rate of global warming and climate change, while at the same time stimulating economic development and promoting energy from eco-friendly resources. Keywords: Carbon dioxide, Renewable energy, Environmental Kuznets curve. JEL Classifications: Q20, Q30, Q56 DOI: https://doi.org/10.32479/ijeep.7535